Distributed Database Systems in the Dynamic Networks Environment - Janech, Jan; Baca, Tomas (Communications - Scientific letters of the University of Zilina, 2011)
This article describes a new architecture of a distributed database system, which is designed especially for the dynamic networks environment. Problems with the architecture of a traditional distributed database system are explained, and a solution is offered. The architecture introduced in this article does not intend to be a universal database system. It is a specialized solution for the implementation of distributed database systems in the dynamic networks environment.